Male and mosquito larvae survey at the Arenal-Tempisque irrigation project, Guanacaste, Costa Rica - Vargas V, Mario (2003)
A monitoring of male and larvae of mosquitoes was conducted during 1991-1994, at the Irrigation Project in Arenal-Tempisque, Guanacaste, Costa Rica. CDC CO2-baited traps were used to collect adults of mosquitoes and dips were used for immatures of culicids. A total of 1 480 larvae and 1 129 males of culicids were identified resulting in, Aedes with 6 species, Anopheles, Mansonia and Psorophora with 2 species, Culex with 21 species and Haemagogus, Limatus, Toxorhynchites and Uranotaenia with only one species each. The results indicate that, as occurred in other countries, irrigation projects must be under strict monitoring programs to prevent and control possible health problems in which mosquitoes act as vectors